PENGARUH LOCUS OF CONTROL TERHADAP HUBUNGAN KOMITMEN PROFESIONAL DAN KEPUASAN KERJA AKUNTAN PENDIDIK - Restuningdiah, Nurika (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
The Influence of Locus of Control on The Relationship between Professional Commitment And The Job Satisfaction Of Accountant Academician. The effect of locus of control on the relationship between professional commitment and job satisfaction were investigated, because there has not been consistently empirical research. As suggested in the literature, this research tests hypotheses that these specific contingency factor should aid in identifying situations where professional commitment would have a strong relationship with job satisfaction. Analysis of 41 accountant academician, who becomes the respondents, indicated that professional commitment has direct relationship with job satisfaction. In addition, the contingency factor was found to play key role on this relationship. The result of moderated regression analysis proved that locus of control to be pure moderator variable, and has a negative effect to the relationship between professional commitment and job satisfaction, so that the relationship between professional commitment and job satisfaction was significantly stronger for accountant academician with internal locus of control than in accountant academician with external locus of control. The implication of this study is relevant to university management and to academicians seeking to explain how, when, and where professional commitment is needed.Key words: job satisfaction, locus of control professional commitment